PEMBUATAN KARYA 11 TEKNIK DASAR FOTOGRAFI DENGAN MEMAKSIMALKAN FITUR KAMERA PADA HANDPHONE - Hans Hermang Mintana (Jurnal Ilmu Komunikasi AKRAB, 2022)
The increasing use of cell phones greatly affects the use of camera features. This hasgreat potential in increasing the number of people who want to learn photography. Mobilephone photography is usually used to capture moments that occur in public spaces.Utilization of this cell phone camera feature can actually be used to produce commercialworks. The technique used also refers to the basic techniques of photography. This techniqueis a basic technique that uses minimal equipment in shooting, the basic equipment onlyrelies on the camera. Another approach in making this work is to use 11 basic photographytechniques.The 11 basic techniques of photography are divided into three parts, namely thebasic techniques of light, the basic techniques of motion and the basic techniques of sharpspace. The basic light techniques are divided into front light, side light, back light andsilhouette. The basic techniques of motion are divided into stop action, slow action, panningand bulbing. The basic techniques of sharp space (def/depth of field) are divided into narrowdof, wide dof and selective focus. The author only relies on sunlight in the process of makingthis work. So the author needs to be careful in choosing the shooting time to suit the desiredlight conditions.The process of making this work relies on the use of a mobile phone camera fromthe Xiaomi Redmi Note 11. The creation of this work produces 11 works with 1 work each oneach basic photography technique